Realizing Corporate Social Responsibility Based on the Expanded Balanced Scorecard - LI, XUN (2017)
The objective of enterprise management has witnessed tremendous evolvement over the years. Enterprises pay more and more attention to the fact that the concern for society or environment need to be integrated into the business strategy at the beginning, which can contribute to the competitive advantage in modern society. Activities such as expansion of market, employees’ development, acceleration of inventions and novel ideas, are what an enterprise can achieve with the competitive advantage. To enhance the understanding of this phenomenon, this article researches the importance of corporate social responsibility (CSR) in order to promote strategic updates and organizational change, at the same time, support the sustainable development of society more widely. This article delves into understanding how corporate social responsibility benefit from the balance scorecard. Drawing on data gathered from Chinese listed company, the author provides insights into the structures and processes that companies employ to design, implement and monitor their CSR strategy. Aside the unearthing of the connection that exists between expanded balanced scorecard and the management of CSR, this article also leads to the author’s presentation of evidence on the methods employed by organizations in actualizing their CSR goals, which may become valuable for real companies looking to put proper CSR into practice.